Strategic business models to support demand, supply, and destination management in the tourism and hospitality industry - Carvalho, Luisa Cagica 1970-; Calisto, Lurdes 1965-; Gustavo, Nuno 1978- (IGI Global, 2020)
"This book examines emerging, innovative, and strategic business models to support demand, supply, and destination management in the tourism hospitality industry"--